Kindergarten Teachers’ Mindfulness in Teaching and Job Satisfaction: A Moderated Mediation Model - Pan Yin; Chao Huang; Xiaochun Yin; Fengwan Yang; Shi Qiu; Daixue Song (SAGE Open)
Based on the theory of meaning construction, this research aims to examine the relationship between mindfulness-based instruction and job satisfaction among educators working in kindergarten settings. Specifically, this study will evaluate whether teachers’ self-efficacy mediates this relationship and explore the potential moderating impact of role maladjustment on this mediation process. A total of 531 kindergarten teachers, mostly females participated in the study by responding to self-administered questionnaires measuring their mindfulness in teaching, teachers’ self-efficacy, role maladjustment, and job satisfaction. The findings indicate that there is a notable and favorable correlation between the practice of mindfulness in teaching and job satisfaction among kindergarten teachers. Additionally, the analysis suggested that teachers’ self-efficacy partially mediated this relationship. These results remained significant even after controlling for demographic variables. Further examination using moderated mediation analysis indicated that role maladjustment did not have a moderating effect on either the direct or indirect links between mindfulness in teaching and job satisfaction. The results highlight the importance of teacher self-efficacy as a mediating factor, emphasizing the role of mindfulness in assisting preschool educators in effectively managing challenges and adversities. This, in turn, enhances emotional regulation and coping skills while cultivating a heightened awareness of personal strengths and abilities, ultimately resulting in greater job satisfaction.